Cancer Rehabilitation: Do Functional Gains Relate to 60 Percent Rule Classification or to the Presence of Metastasis?. Issue 2 (2nd July 2015) - Sliwa, James A.; Shahpar, Samman; Huang, Mark E.; Spill, Gayle; Semik, Patrick
Abstract: Background: Literature supporting the benefits of inpatient rehabilitation for cancer patients is increasing. Many cancer patients, however, do not qualify for inclusion in the Centers for Medicare and Medicaid 60% rule and consequently may not receive services. The benefit of inpatient rehabilitation in this specific cancer group has not been investigated and is the focus of this study. Objective: To investigate functional gains made during inpatient rehabilitation by patients impaired by cancer, and to compare the functional gains made during inpatient rehabilitation for patients impaired by cancer in relation to the presence or absence of metastatic disease and compliance or noncompliance with the Medicare 60% rule. Setting: Freestanding university‐affiliated rehabilitation hospital. Participants: A total of 176 adult patients admitted for inpatient rehabilitation due to cancer. Methods: Retrospective chart review of patients admitted for inpatient rehabilitation with deficits identified related to cancer. Main Outcome Measures: Demographic data including cancer type, presence of metastasis, age, gender, marital status, ethnicity, length of stay (LOS), discharge destination, and transfer to acute care. Functional status including admission and discharge Functional Independence Measure Score (FIM), total, motor, and cognitive FIM gains, total, motor, and cognitive FIM efficiency for the study sample, for patients with and without a diagnosis compliant with the 60% rule and for patients with and without metastatic disease. Results: In all, 176 cases met inclusion criteria. An admission coded diagnosis that was compliant with the 60% rule was present in 97 cases (55.1%). In 153 cases, the presence or absence of metastatic disease was known. Metastatic disease was present in 69 cases (45%). All groups (total sample, metastatic versus nonmetastatic, compliant versus noncompliant) made significant functional gains. Patients with a diagnosis noncompliant with the 60% rule had higher admission total FIM ( P = .001), discharge total FIM ( P = .014), admission motor FIM ( P = .005), admission cognitive FIM ( P = .008), and discharge cognitive FIM ( P < .001) scores than those with a compliant diagnosis. Patients with metastatic disease had higher admission total FIM ( P = .026) and admission ( P = .001) and discharge ( P = .02) cognitive FIM scores than patients with nonmetastatic disease. There were no significant differences between groups regarding total, motor, or cognitive FIM gains or total motor or cognitive FIM efficiencies. Differences in age, length of stay, and admission motor and discharge FIM scores between groups were related to cancer types and source of impairment. Conclusion: Patients with functional limitations resulting from cancer or its treatment made significant functional gains in inpatient rehabilitation. There were no significant differences in functional gains made by those with or without metastatic disease or those compliant versus noncompliant with the 60% rule. The presence of metastatic disease or a diagnosis not compliant with the 60% rule does not preclude cancer patients from making significant functional gains.